Investigation on Sedan Car Accident Crashed into the Back of an 18-Wheel Semi-trailer Truck Carrying a Container on Bang Kruai-Sai Noi Road, Mueang Nonthaburi District, Nonthaburi Province - Angkanasopit , Sunti (Medical Journal of Sakon Nakhon Hospital, 2024)
The Ambulance Operation Center (AOC) of Phra Nang Klao hospital, Nonthaburi province, received a report of an accident in May 2024. The accident involved a sedan rear-ending an 18-wheel semi-trailer truck carrying a container. Two fatalities were reported at the scene. The accident occurred in front of a Noodle Restaurant on Bang Kruai-Sai Noi Road in Mueang Nonthaburi district, Nonthaburi province, during a period of post-rain conditions. The injury investigation team of the Ambulance Operation Center (AOC), Phra Nang Klao hospital, conducted an investigation into the injuries and fatalities caused by this road accident to identify preventive measures to avoid future accidents. Data collection was gathered by using medical records, site surveys of the accident scene, vehicle condition assessments, interviews with the survivors, and first responders. Analysis of contributing factors to injuries was performed by using the Haddon’s Matrix Model. The investigation revealed that two fatalities were reported at the scene. The deceased included the driver of the sedan, aged 57, and a passenger, aged 95. The accident is presumed to have been caused by the sedan driver’s reckless behavior, including high-speed driving on wet and slippery road conditions after rainfall, combined with rapid lane changes. Despite the vehicle's braking assistance system, the wet road surface likely caused the car to skid uncontrollably, resulting in a severe impact that damaged the vehicle extensively, including the passenger cabin. The severity of the injuries led to fatalities for both the driver and the passenger.